Correction: O2-3-Aminopropyl diazeniumdiolates suppress the progression of highly metastatic triple-negative breast cancer by inhibition of microvesicle formation via nitric oxide-based epigenetic regulation. Issue 3 (6th January 2020) - Kang, Fenghua; Zhu, Jiayi; Wu, Jianbing; Lv, Tian; Xiang, Hua; Tian, Jide; Zhang, Yihua; Huang, Zhangjian
Abstract : Correction for ' O 2 -3-Aminopropyl diazeniumdiolates suppress the progression of highly metastatic triple-negative breast cancer by inhibition of microvesicle formation via nitric oxide-based epigenetic regulation' by Fenghua Kang et al., Chem. Sci., 2018, 9, 6893–6898.